USER CENTERED DESIGN PADA AUGMENTED REALITY UNTUK MENDUKUNG SISWA DALAM PEMBELAJARAN BANGUNAN BERSEJARAH DI JAWA BARAT - Syahbaniar Rofiah; Dadan Sukma; Ina Maryani (Evolusi : Jurnal Sains dan Manajemen, 2019)
Abstract -  In the teaching and learning process on historical subjects students are sometimes less interested in understanding the material. To stimulate the visuals of these students learning media must look attractive. The absorption of teaching materials is very important for students in understanding the material so that the selection of appropriate learning media can facilitate students for this. By utilizing technology as a learning medium can build an interactive atmosphere between students and teachers. Students can not only read books or listen to explanations of material by the instructor but can interact with the objects described in the teaching material. The teaching staff also contributes in making this happen so a teacher at least knows the current technological developments. In these problems the need for the selection of appropriate learning media. By using the User Centered Design (UCD) method, we can find out the level of usability mockup from the learning media of historic buildings in West Java. From the evaluation results of the learning media of historic buildings according to table 2. The lowest percentage is 0.71% in the sound quality in the delivery of material explanation and button usage while the highest percentage in the duration of time according to learning is 60.71% so that the application will be improved according to user needs to be better.Keywords— Android, Historic Buildings, Learning Media, User Centered Design. Abstrak - Dalam proses belajar mengajar pada mata pelajaran sejarah siswa terkadang kurang tertarik untuk memahami materi. Untuk merangsang visual dari siswa tersebut media pembelajaran harus terlihat menarik. Penyerapan materi ajar sangat penting bagi siswa dalam memahami materi sehingga pemilihan media pembelajaran yang tepat dapat memudahkan siswa untuk hal tersebut. Dengan memanfaat teknologi sebagai media pembelajaran dapat membangun suasana interaktif antara siswa dan pengajar. Siswa tidak hanya dapat membaca buku atau mendengarkan penjelasan materi oleh pengajar akan tetapi dapat berinteraksi dengan dengan objek yang dijelaskan dalam materi ajar. Tenaga pengajar juga turut andil dalam mewujudkan hal tersebut untuk itu seorang pengajar minimal mengetahui perkembangan teknologi saat ini. Dalam permasalahan tersebut perlunya pemilihan media pembelajaran yang tepat. Dengan menggunakan metode User Centered Design (UCD) dapat mengetahui seberapa tingkat usability mockup dari media pembelajaran bangunan bersejarah di Jawa Barat. Dari hasil evaluasi media pembelajaran bangunan bersejarah sesuai dengan tabel 2. Persentase yang paling rendah 0,71% pada kualitas suara dalam pengantaran penjelasan materi dan penggunaan button sedangkan persentasi paling tinggi pada durasi waktu sesuai pembelajaran sebesar 60,71% sehingga aplikasi akan diperbaiki sesuai dengan kebutuhan pengguna agar lebih baik.Kata kunci—Android, Bangunan Bersejarah, Media Pembelajaran, User Centered Design